Combined application of gamma radiation, cleaning and chemical sanitizers in decontamination of vehicle air conditioning filters (Brazilian Journal of Radiation Sciences (BJRS), 2023)
This work aimed to analyze the fungal contamination of air-conditioning filter waste (n=15) as an indicator of Quality Air Indoor from different car models in São Paulo city in São Paulo State, Brazil, during the period from October 2018 to July 2019. Three different treatments were used for the decontamination of car air conditioning filters, such as mechanical vacuum cleaning (I), vacuum cleaning and use of sanitizing product (II), and sanitizing product associated with radiation treatment at a dose of 17 kGy (III). After the treatments, microbiological analyses were performed and samples were plated in Petri dishes containing Sabouraud agar transferred by Swabs, and incubated for 7 days at 25 °C. The Petri dishes were stored in a standard Biochemical Oxygen Demand incubator, for the growth of fungal cultures. After incubation, the fungal cultures were evaluated, and the fungal counting was expressed in unit-forming colonies (UFC) and frequency in samples (%). The fungi were examined by lactophenol blue solution staining for microscopy. All samples of treatment I and II were contaminated with various fungal genera and high bioburden, namely (treatment I) Alternaria alternata, Aspergillus flavus, A. niger, Cladosporium spp., Fusarium spp., Mucor spp., Nigrospora spp., Not Sporulated Fungi (NSF), Penicillium spp., Rhizopus spp., Rhodotorula spp., Trichoderma spp. and yeasts. Treatment II showed Alternaria alternata, Aspergillus flavus, A. fumigatus, A. niger, A. ochraceus, Cladosporium spp., Mucor spp., NSF, Penicillium spp., Phoma spp., Rhizopus spp., Rhodotorula spp., Trichoderma spp., and yeasts. Treatment III presented NSF and yeasts, with 80% of material decontamination.